(untitled) (Nexus International Journal of Science and Education, 2024)
The current study aimed to explore the lived experiences of the teachers as regard to their technology integration in new normal learning set-up and how they cope up with challenges. In this study, the researcher selected the 12 public elementary school teachers in Laak South District, Davao de Oro as the participants of the study. Purposive sampling technique sampling technique was utilized in the selection of the participants. Qualitative research design using phenomenological method was employed. The data collected were thematics analysis. Findings revealed that on the lived experiences of the teachers as regard to the technology integration knowledge within COVID-19 crisis set-up, the emerging theme was Adaptation to Online Teaching with subthemes namely: technological proficiency and skills development; pedagogical innovations and experimentation; and lesson planning and curriculum adaptation. In addition, the theme that emerged on the participants’ coping mechanism with regards to the challenges in relation to technology integration knowledge within COVID-19 crisis was Professional Development for Remote Learning with subthemes namely: online workshops and training; individualized professional development plans; and peer learning communities. Lastly, the emerging themes on the skills developed among public elementary school teachers were digital literacy enhancement; curriculum integration; and tech tools exploration. The study, therefore, conducted for further utilization of findings through publication in reputable research journal.